Impact of Wet–Dry Cycles on the Durability and Degradation Mechanisms of Recycled Aggregate Concrete With Varying Replacement Percentages - Changhao Huang; Hao Du; Peichen Cai; Xiaoyu Wang; Zhao Chen; Ke Lou; Shengjie Wang; Xuesong Mao; Feiheng Huang; Qian Wu (Advances in Civil Engineering)
This study addresses the durability concerns of concrete subjected to wet–dry cycles, particularly focusing on the impact of different recycled aggregate (RA) replacement percentages. Concrete is increasingly used with RAs for sustainability. However, its long-term performance under environmental stress is not fully understood. The primary motivation of this study is to provide a comprehensive understanding of how varying replacement percentages of RAs influence concrete degradation, a key factor for improving material performance in real-world applications. Through a series of wet–dry cycle tests, we analyze key degradation indicators, including surface texture changes, mass loss, and compressive strength. The study findings reveal that wet–dry cycles significantly alter the concrete surface, with higher RA content leading to more extensive pore formation, cracks, and surface roughness. Initially, concrete mass increases slightly due to water absorption, but after several cycles, mass loss becomes significant, particularly for higher replacement percentages, which is attributed to internal pore damage and degradation of the interface between the RAs and cement paste. Furthermore, the compressive strength declines steadily with increasing cycles, with more severe deterioration at higher replacement percentages. This decline is primarily due to microcrack propagation and degradation of the interfacial transition zone. A degradation model is developed to quantify the relationship between RA content and durability loss, offering practical recommendations for optimizing replacement percentages to balance sustainability and durability. This study provides valuable insights into enhancing the long-term performance of concrete in environments exposed to wet–dry cycles.